SUDUT PANDANG DALAM KARYA LUKIS DENGAN TEKNIK REALIS KONTEMPORER - Pramuji Susatio, Dra. Jupriani, M.Sn., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2017)
Viewpoint is to see something, mean something to others by thinking. Every man is not free from problems, in everyday life we can see how the perspective of each person is different. The goal is to create or visualize paintings with the object of human figures through paintings by contemporary realist technique. This thesis was made through five stages, namely preparation phase (exploration), phase penetepan ideas (elaboration), the synthesis, the realization of the concept and stages of completion. The work achieved by the title of neglect, loneliness, lying, excellence, just us, compassion, and entangled. The work achieved by the title of the mirror, the light spot, blur, guns life, race, selfish, views, wasted, masks, limited eye. The title is taken from a condition that occurs in this current era. This work is made manually producing work that is unique and has artistic value that can be used to beautify the room. I hope these ideas and techniques can be developed by writers or other writers in the future.Kata kunci: Seni Lukis, Sudut Pandang, Kontemporer